1993
DOI: 10.1177/000456329303000406
|View full text |Cite
|
Sign up to set email alerts
|

Serum Total Sialic Acid and Lipid-Associated Sialic Acid in Normal Individuals and Patients with Myocardial Infarction, and Their Relationship to Acute Phase Proteins

Abstract: Serum total sialic acid (TSA) has gained medical interest, particularly as a cardiovascular risk factor and it has been hypothesized that serum levels relate to serum acute phase proteins, some of which are sialylated. We assayed serum TSA and also lipid associated sialic acid (LASA) in 50 normal individuals (24 male) and 15 subjects (12 male) who had experienced a myocardial infarct. The mean serum TSA in the normal individuals was 2.05 SD 0.38 mmol/L (range 1.16-2.74) and the mean serum LASA was 0.70 SD 0.19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…14,46 Significant increase in total, lipid-bound and protein-bound sialic acids were observed in broilers infected with infectious bronchitis. 21 In the study of Mosleh et al 47 increase in total, lipid-bound and protein-bound sialic acids concentrations were reported after omphalitis in Japanese quail.…”
Section: Discussionmentioning
confidence: 99%
“…14,46 Significant increase in total, lipid-bound and protein-bound sialic acids were observed in broilers infected with infectious bronchitis. 21 In the study of Mosleh et al 47 increase in total, lipid-bound and protein-bound sialic acids concentrations were reported after omphalitis in Japanese quail.…”
Section: Discussionmentioning
confidence: 99%
“…Gokmen et al (42) have suggested that either the shedding or secreting of sialic acid from the cell or cell membrane surface may be partly responsible for an increased serum sialic acid concentration following acute myocardial infarction. The correlation between serum total sialic acid and plasma fibrinogen may explain the association between elevated serum sialic acid and cardiovascular problems (5,34). From these reports it seems that irrespective of the mechanism , serum sialic acid seems to be a causal risk factor and could prove useful in screening of population at cardiovascular risk.…”
Section: Serum Sialic Acidmentioning
confidence: 97%
“…Later on, many studies came up showing that serum sialic acids were elevated in cardiovascular diseases (3)(4)(5)(6)(7)(8)(9)(10). Serum sialic acid levels correlated with carotid atherosclerosis, independently of major cardiovascular risk factors (26).…”
Section: Serum Sialic Acidmentioning
confidence: 99%
“…Increase in the free radical levels also cause increases in the catabolic reactions in cells for the protection of homeostasis in the organisms [15] . Increased free radical levels cause cell and tissue destructions in the organism and elicits a status called "oxidative stress" [4,14,15] .Sialic acid (SA) is a derivative of neuroaminic acid [16,17] and abundantly present in all cell membranes [17][18][19][20] . It has been reported that SA concentration had increased rapidly in the pathologic conditions like inflammation, tissue destruction, and tissue proliferation [17] .…”
mentioning
confidence: 99%
“…Due to this fact, evaluation of SA concentration may be an important sign in the diagnosis of inflammatory diseases [19,[21][22][23][24] . Although the mechanism in the increase of serum SA level during the inflammatory conditions is not clear, many investigators indicated the role of AFPs which share the same structure with SA [17,19,20,25] . Since acute phase reactants are glycoprotein in structure, it has been reported that increase in these proteins affects the TSA levels [20] but not reflects the increases in SA levels exactly, which also bears glycoprotein structure [19] .…”
mentioning
confidence: 99%